Powerful Social Studies Teaching With Poetry and Primary Sources. Issue 1 (2nd January 2017) - Sell, Corey Ranshaw; Griffin, Krista
ABSTRACT: Given the current marginalization of the social studies within elementary classrooms it is vital that elementary educators seek integrative techniques that promote the social studies. This article explores one such example of integration taught by the authors within an elementary classroom. The three-day lesson taught to fifth-grade students aimed to teach a justice-oriented conception of citizenship through the use of historical biographies, found poetry, and primary sources. By the end of the third day, the students had used both general literacy practices (e.g. shared reading, visual literacy, close reading) and disciplinary literacy (e.g. sourcing, contextualizing, corroborating), demonstrating that integration can be a powerful means to teach the social studies while also maintaining the integrity of the disciplines.